CRISPR/Cas12a-powered immunosensor suitable for ultra-sensitive whole Cryptosporidium oocyst detection from water samples using a plate reader. (15th September 2021) - Li, Yi; Deng, Fei; Hall, Tim; Vesey, Graham; Goldys, Ewa M.
Highlights: A CRISPR/Cas12a-based ultra-sensitive whole waterborne pathogen detection method. A hybrid single strand DNA oligo and antibody conjugate targeting the pathogen surface antigen. Capable with plate reader for conventional ELISA assay with same experimental setup. 3 orders of magnitude quantitative detection with maximum single microorganism sensitivity for Cryptosporidium parvum oocysts. Suitable for direct testing of diluted mud samples from water treatment plant. Graphical abstract: Image, graphical abstract Abstract: Waterborne pathogens, such as Cryptosporidium parvum, pose a major threat to public health globally, and this requires screening of drinking and environmental water for low number of contaminating microbes. However, current detection approaches generally require trained experts with sophisticated instruments, and are not suitable for large-scale screening and rapid outbreak response. Recent advances in ultrasensitive CRISPR/Cas-based biosensing continue to expand the range of detectable molecular targets, however single microbes could not be directly detected so far, especially in environmental samples. Here, we report an ultrasensitive CRISPR/Cas12a-powered immunosensing method suitable for microbial detection which links antibody-based recognition with CRISPR/Cas12a-based fluorescent signal amplification through an antibody-DNA conjugate. This approach is shown here to detect whole 4 µm size Cryptosporidium parvum oocysts with a linear range from 6.25 – 1600 oocysts/mL, at a maximum sensitivity of single oocyst per sample. Its potential to apply to various complex sample matrices has also been demonstrated. After sample dilution by factor of 10, we were able to detect 10 oocysts from a back-wash mud samples from water treatment plate. This method uses the same experimental setup (plate reader) as a conventional ELISA assay thus reducing the need for microscopy-based identification of Cryptosporidium, which represents the gold-standard but requires high level expertise and time-consuming manual counting. This work highlights the potential of CRISPR/Cas-based biosensing for water quality assessment and ultrasensitive whole pathogen detection.